2010
DOI: 10.1261/rna.2307710
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of translation by cytotrienin A—a member of the ansamycin family

Abstract: The ansamycins are a diverse and often physiologically active group of compounds that include geldanamycin and rifamycin, inhibitors of heat shock protein 90 and prokaryotic DNA-dependent RNA synthesis, respectively. Cytotrienin A is an ansamycintype small molecule with potent antiproliferative and proapoptotic properties. Here, we report that this compound inhibits eukaryotic protein synthesis by targeting translation elongation and interfering with eukaryotic elongation factor 1A function. We also find that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…17,18 Recently, it has been shown that cytotrienin A inhibits eukaryotic protein synthesis by targeting translation elongation and interfering with eukaryotic elongation factor 1A function. 15 Consistent with this and our findings, 15,16 mycotrienin II and its structural derivatives inhibited cellular protein synthesis and cell-free translation. Nevertheless, the de novo protein synthesis in intact living cells (Figure 2a) was inhibited much more strongly by mycotrienin II than the cell-free translation ( Table 1).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…17,18 Recently, it has been shown that cytotrienin A inhibits eukaryotic protein synthesis by targeting translation elongation and interfering with eukaryotic elongation factor 1A function. 15 Consistent with this and our findings, 15,16 mycotrienin II and its structural derivatives inhibited cellular protein synthesis and cell-free translation. Nevertheless, the de novo protein synthesis in intact living cells (Figure 2a) was inhibited much more strongly by mycotrienin II than the cell-free translation ( Table 1).…”
Section: Discussionsupporting
confidence: 90%
“…The difference in sensitivity is in agreement with the observation that cytotrienin A inhibits cellular protein synthesis more strongly than the cell-free translation. 15 This may be because the cell-free translation systems contain larger amounts of proteins that bind to mycotrienin II or cytotrienin A (most likely eukaryotic elongation factor 1A) than living cells, and therefore higher concentrations of the compounds are required for the inhibition of translation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The polysome profile was unchanged in cells treated with 4 compared to DMSO control ( Figure 2c , left panel), indicating that global translation initiation was not perturbed. To test for inhibition of translation elongation, we asked whether 4 could abrogate polysome runoff induced by the initiation inhibitor harringtonine ( Lindqvist et al, 2010 ). Similar to the known elongation inhibitor cycloheximide, pretreatment of cells with 4 completely blocked harringtonine-induced polysome depletion (2c, right panel).…”
Section: Resultsmentioning
confidence: 99%
“…These were cytotrienin A (CytA), an ansamycin compound chemically distinct from DidB ( Fig. 4 C ) that we previously showed inhibits translation elongation specifically by interfering with eEF1A function ( Lindqvist et al, 2010 ) and cycloheximide (CHX), an elongation inhibitor that targets the ribosome ( Robert et al, 2009 ). CytA had similar effects to DidB in inducing nuclear accumulation of AID-GFP, but not GFP-APOBEC1, in HeLa cells, whereas CHX did not affect either protein ( Fig.…”
Section: Resultsmentioning
confidence: 99%